Time for Action: Collaborating for Better Oral Health - Candace Jones, RDH, MPH; Jane Weintraub, DDS, MPH; Stuart Lockwood, DMD, MPH; (Blackwell Synergy, 2003)
If the vibrant energy and enthusiasm seen in Milwaukee was any indication of the potential for collaboration among those interested in advancing oral health, then the future is bright for dental public health and optimal oral health for all. The time for action is now and the 2003 National Oral Health Conference (NOHC) met the challenge.